Risk Factors for Return to the Emergency Department and Readmission in Patients With Hospital-Diagnosed Advanced Lung Cancer. Issue 4 (3rd April 2023) - Ray, Emily M.; Hinton, Sharon P.; Reeder-Hayes, Katherine E.
Abstract : Background: Advanced lung cancer (ALC) is a symptomatic disease often diagnosed in the context of hospitalization. The index hospitalization may be a window of opportunity to improve care delivery. Objectives: We examined the patterns of care and risk factors for subsequent acute care utilization among patients with hospital-diagnosed ALC. Research Design, Subjects, and Measures: In Surveillance, Epidemiology, and End Results-Medicare, we identified patients with incident ALC (stage IIIB–IV small cell or non–small cell) from 2007 to 2013 and an index hospitalization within 7 days of diagnosis. We used a time-to-event model with multivariable regression to identify risk factors for 30-day acute care utilization (emergency department use or readmission). Results: More than half of incident ALC patients were hospitalized around the time of diagnosis. Among 25, 627 patients with hospital-diagnosed ALC who survived to discharge, only 37% ever received systemic cancer treatment. Within 6 months, 53% had been readmitted, 50% had enrolled in hospice, and 70% had died. The 30-day acute care utilization was 38%. Small cell histology, greater comorbidity, precancer acute care use, length of index stay > 8 days, and prescription of a wheelchair were associated with higher risk of 30-day acute care utilization. Age >85 years, female sex, residence in South or West regions, palliative care consultation, and discharge to hospice or a facility were associated with lower risk. Conclusions: Many patients with hospital-diagnosed ALC experience an early return to the hospital and most die within 6 months. These patients may benefit from increased access to palliative and other supportive care during index hospitalization to prevent subsequent health care utilization.